2014
DOI: 10.1007/s11356-013-2461-8
|View full text |Cite
|
Sign up to set email alerts
|

Sources and mass fluxes of the main contaminants in a heavily polluted and modified river of the North China Plain

Abstract: Many rivers in China and other newly industrialized countries have suffered from severe degradation of water quality in the context of rapid economic growth. An accounting method was developed to investigate the source and mass fluxes of the main contaminants in the Ziya River, a severely polluted and heavily modified river in a semiarid area of the North China Plain, where chemical oxygen demand (COD) and ammonia nitrogen (NH 4 -N) were the most important indicators of pollution. The results showed that the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…Studies from relatively undisturbed watersheds indicated that AN in rivers usually accounts for about 10 % (or even less) of total nitrogen (Li et al, 2009;Singh et al, 2005), while it can be higher than 70 % in urban or heavily polluted rivers in Asia (Li et al, 2014;Pernet-Coudrier et al, 2012). Evidence from the long-term monitoring studies in the mainstream of Huai River revealed that AN was the major form of dissolved nitrogen before 2000 (Mao et al, 2003).…”
Section: Implications For Percent Tn Exportmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from relatively undisturbed watersheds indicated that AN in rivers usually accounts for about 10 % (or even less) of total nitrogen (Li et al, 2009;Singh et al, 2005), while it can be higher than 70 % in urban or heavily polluted rivers in Asia (Li et al, 2014;Pernet-Coudrier et al, 2012). Evidence from the long-term monitoring studies in the mainstream of Huai River revealed that AN was the major form of dissolved nitrogen before 2000 (Mao et al, 2003).…”
Section: Implications For Percent Tn Exportmentioning
confidence: 99%
“…This is problematic, because in many heavily impacted rivers, e.g., with high biological oxygen demand (BOD) due to untreated sewage and other sources of organic pollutants, the correspondingly low dissolved oxygen levels can provide an environment suitable for the persistence of AN as a component of riverine N fluxes. For example, in heavily polluted rivers in some regions, AN can account for more than 70 % of total nitrogen across seasons and river sections (Pernet-Coudrier et al, 2012;Li et al, 2014). Furthermore, in many Chinese rivers, AN is the only component of riverine N that is regularly monitored (Ma et al, 2009;Xia et al, 2011;Shao et al, 2006), which indicates the prevalence of the problem and supports the need for better understanding of AN dynamics in these heavily impacted rivers.…”
Section: Introductionmentioning
confidence: 97%
“…Chanpiwat and Sthiannopkao (2014) reported the source of water contamination by heavy metals like Al, Cd, Co, Mn, Ni, Pb and Zn were industrial and household activities in Southeast Asian aquatic environs. Li et al (2014) highlighted the release of urban sewage with high COD and ammoniacal-nitrogen concentration were as significant source of contamination in riverine environs of China. Beldean-galea et al (2016) highlighted the occurrence of polycyclic aromatic hydrocarbons due to pyrogenic and petrogenic sources of water pollution.…”
Section: Water Quality and Anthropogenic Sourcesmentioning
confidence: 99%
“…Chanpiwat and Sthiannopkao (2014) reported the source of water contamination by heavy metals like Al, Cd, Co, Mn, Ni, Pb and Zn were industrial and household activities in Southeast Asian aquatic environs. Li et al (2014) highlighted the release of urban sewage with high COD and ammoniacal-nitrogen concentration were as significant source of contamination in riverine environs of China. Beldean-galea et al (2016) highlighted the occurrence of polycyclic aromatic hydrocarbons due to pyrogenic and petrogenic sources of water pollution.…”
Section: Water Quality and Anthropogenic Sourcesmentioning
confidence: 99%